Pengaruh Literasi Keuangan, Experience Regret dan Perceived Risk terhadap Keputusan Investasi pada Mahasiswa Indonesia - Alfin Febrianti; H. Isnurhadi; Isni Andriana (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to determine the influence of Financial Literacy, Experience Regret and Perceived Risk on Investment Decisions in Students in Indonesia (case study of KMI Expo XII 2021 participants). The population in this study is students who participated in Indonesian Student Entrepreneurship (KMI EXPO XII 2021) where there are 94 Universities. This study used the purposive clepling technique. The data used in this study is primary data and secondary data with data collection techniques through questionnaires. The data analysis technique used is multiple linear regression analysis. Based on the results of the study, it shows that financial literacy has a negative and significant effect on investment decisions, experience regret has a positive effect and does not have a significant effect on investment decisions and peceived risk has a positive and significant effect on investment decisions for students in Indonesia participating in KMI Expo XII 2021.